The comparison of selected legal aspects of insurance products on the Polish and British markets - Barszowski, Sebastian (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Author of this thesis has undertaken the research about Polish and English legal system and regulations that are essential for insurance market. This topic is not very popular in literature, because it is hard to find the comparison of Polish and English regulations that establish the conditions on which third party liability vehicle insurance contracts are concluded. That issue is very important to determine the level of development of the Polish insurance market. Before 1989 insurance market in Poland was monopolized by two companies. So it could be said that it is rather young, and may be less developed than English. The aim of that thesis has been achieved. The studies show that there are several significant differences in Polish and English legal system, but regulations do not follow changes of the insurance market in both countries. At the beginning of the thesis the author presented history of risk management and insurances. Next moved to analysis of legal regulations that are essential for compulsory vehicle insurance in Poland and England.